2008
DOI: 10.1371/journal.pntd.0000281
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba Shows Reversible Variation in Ploidy under Different Growth Conditions and between Life Cycle Phases

Abstract: Under axenic growth conditions, trophozoites of Entamoeba histolytica contain heterogenous amounts of DNA due to the presence of both multiple nuclei and different amounts of DNA in individual nuclei. In order to establish if the DNA content and the observed heterogeneity is maintained during different growth conditions, we have compared E. histolytica cells growing in xenic and axenic cultures. Our results show that the nuclear DNA content of E. histolytica trophozoites growing in axenic cultures is at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 28 publications
(44 reference statements)
1
51
0
Order By: Relevance
“…First, E. histolytica infection results in disruption of the mucosal barrier, which might lead to infiltration of bacteria into the lamina propria. Second, trophozoites feed on gut flora; hence, invading parasites could carry bacterial products, including LPS (46,47). As reported previously, EhMIF in combination with LPS increased TNF-␣ production by macrophages in vitro.…”
Section: Fig 3 Ehmif Immunomodulates Macrophages (A)supporting
confidence: 57%
“…First, E. histolytica infection results in disruption of the mucosal barrier, which might lead to infiltration of bacteria into the lamina propria. Second, trophozoites feed on gut flora; hence, invading parasites could carry bacterial products, including LPS (46,47). As reported previously, EhMIF in combination with LPS increased TNF-␣ production by macrophages in vitro.…”
Section: Fig 3 Ehmif Immunomodulates Macrophages (A)supporting
confidence: 57%
“…Upon further passage, the bacterial populations may change and whether certain bacterial species predominate is not known. It has been observed for some recently axenized E. histolytica clinical isolates that bacterial flora, when provided exogenously, is beneficial to inducing encystation (Mukherjee et al, 2008). Furthermore, it has also recently been demonstrated that there is differential DNA content in parasites grown as long-term axenic cultures compared with those grown under xenic conditions (Mukherjee et al, 2008).…”
Section: Recent Advances In Characterizing Amebic Developmentmentioning
confidence: 99%
“…As an example, cell division in Entamoeba is poorly understood, especially related to our understanding of the mechanism regulating chromatin pairing and segregation during cell division. Entamoeba exist as multinucleated polyploid cells in vitro and in vivo 66 , suggesting that the parasites are able to mitigate issues arising due to gene copy number. Given the atypical cell cycle in Entamoeba 33 , one could be enticed to hypothesize that amoebic RNA is involved in genome stabilization during cellular division.…”
Section: Molecular Methods Regulating Parasite Gene Expressionmentioning
confidence: 99%